2017
DOI: 10.1364/boe.8.003440
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning based, automated segmentation of macular edema in optical coherence tomography

Abstract: Evaluation of clinical images is essential for diagnosis in many specialties. Therefore the development of computer vision algorithms to help analyze biomedical images will be important. In ophthalmology, optical coherence tomography (OCT) is critical for managing retinal conditions. We developed a convolutional neural network (CNN) that detects intraretinal fluid (IRF) on OCT in a manner indistinguishable from clinicians. Using 1,289 OCT images, the CNN segmented images with a 0.911 cross-validated Dice coeff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 306 publications
(187 citation statements)
references
References 29 publications
3
165
1
1
Order By: Relevance
“…For example even an expert might not provide the exact same ratings each time they see the same image, while an algorithm will. This is in line with findings from (Lee et al, 2017c), showing that the agreement between an algorithm and any one expert can be equivalent to agreement between any pair of experts. We have demonstrated that while an individual citizen scientists may not provide reliable results, by intelligently combining a crowd with machine learning, and keeping an expert in the loop to monitor results, decisions can be accurately scaled to meet the demands of Big Data.…”
Section: Scaling Expertise Through Interactions Between Experts Citisupporting
confidence: 90%
See 1 more Smart Citation
“…For example even an expert might not provide the exact same ratings each time they see the same image, while an algorithm will. This is in line with findings from (Lee et al, 2017c), showing that the agreement between an algorithm and any one expert can be equivalent to agreement between any pair of experts. We have demonstrated that while an individual citizen scientists may not provide reliable results, by intelligently combining a crowd with machine learning, and keeping an expert in the loop to monitor results, decisions can be accurately scaled to meet the demands of Big Data.…”
Section: Scaling Expertise Through Interactions Between Experts Citisupporting
confidence: 90%
“…Modeled loosely on the human visual system, CNNs can be trained for a variety of image classification and segmentation tasks using the same architecture. For example, the U-Net (Ronneberger et al, 2015) which was originally built for segmentation of neurons in electron microscope images, has also been adapted to segment macular edema in optical coherence tomography images (Lee et al, 2017b), to segment breast and fibroglandular tissue (Dalmış et al, 2017), and a 3D adaptation was developed to segment the Xenopus kidney (Ç içek et al, 2016). Transfer learning is another broadly applicable deep learning technique, where a number of layers from pretrained network are retrained for a different use case.…”
Section: Introductionmentioning
confidence: 99%
“…A convolutional neural network was trained to learn the mapping between different MRI images in a training set (n=338). We used a U-net architecture (7) , with loss evaluated on "perceptual loss" (9) : the activation of the first layer of a pretrained VGG16 network (11) , a cost function that induces image similarity and prevents over-smoothing. Training used the Adam optimizer (learning rate: 0.0002).…”
Section: Methodsmentioning
confidence: 99%
“…We used deep learning (DL) algorithm to learn the complex mappings between different MRI contrasts. DL has been successful in many different domains (3) , and there are several previous applications of DL in biomedical imaging (4) , including classification of disease states (5) and segmentation of tissue-type (6) lesions (7) and tumors (8) . DL algorithms that take an image as input and generate another image as output have been used for style-transfer: retaining the content of an image, while altering its style to match the style of another image (9) .…”
Section: Introductionmentioning
confidence: 99%
“…In der hier vorgestellten Studie [3] wird ein solcher Deep-Learning-Algorithmus für die automatische Erkennung von typischen Veränderungen bei OCT-Bildgebungsdaten verwendet, die für das Vorliegen einer altersbedingten Makuladegeneration (AMD) sprechen. Dazu verglichen die Arbeitsgruppe Lee et al 52 690 retinale OCT-Scans von Patienten mit Normalbefunden mit 48 312 OCT-Scans von Patienten, bei denen eine AMD vorlag.…”
Section: Transfer In Die Praxis Von Dr Sebastian Siebemann (Köln)unclassified